2018
DOI: 10.1021/acsaem.7b00190
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Thermoelectric Device Based on Poly(ether-b-amide12) and High-Purity Carbon Nanotubes Mixed Bilayer Heterogeneous Films

Abstract: Thermoelectric (TE) generators are an appealing, ecofriendly energy harvesting technology capable of converting temperature gradients into electricity. Carbon nanotube (CNT) filled organic composites typically offer the best potential for making cheaper TE materials. In this study, a block copolymer poly­(ether-b-amide12) (PEBA) with excellent flexibility and mechanical properties was used to fabricate TE materials via blending CNTs. After doping PEBA with lithium chloride (PEBA-Li+), two types (p-type and n-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Compared with inorganic TE materials, the low Seebeck coefficient limits the TE performance of PEDOT:PSS. In some studies, inorganic TE materials with a high Seebeck coefficient or high conductivity are mixed into PEDOT:PSS to improve the TE performance of the composite, but this leads to a decrease in flexibility and stretchability. , Carbon materials, including carbon nanotubes (CNTs) and graphene, are flexible and conductive due to the characteristic structure of the two-dimensional hexagonal lattice of carbon atoms. The strong π–π interaction between CNTs (or graphene) and PEDOT:PSS can effectively improve the conductivity of the composite while maintaining its flexibility. , In addition to conductive polymers, graphene can also be solely mixed into the elastomer to prepare flexible TE materials. The resistance of some graphene-based TE materials is generally sensitive to mechanical strain. Thus, they are more suitable for TE sensors rather than TE generators. , However, most current wearable TE materials are only flexible rather than intrinsically stretchable.…”
mentioning
confidence: 99%
“…Compared with inorganic TE materials, the low Seebeck coefficient limits the TE performance of PEDOT:PSS. In some studies, inorganic TE materials with a high Seebeck coefficient or high conductivity are mixed into PEDOT:PSS to improve the TE performance of the composite, but this leads to a decrease in flexibility and stretchability. , Carbon materials, including carbon nanotubes (CNTs) and graphene, are flexible and conductive due to the characteristic structure of the two-dimensional hexagonal lattice of carbon atoms. The strong π–π interaction between CNTs (or graphene) and PEDOT:PSS can effectively improve the conductivity of the composite while maintaining its flexibility. , In addition to conductive polymers, graphene can also be solely mixed into the elastomer to prepare flexible TE materials. The resistance of some graphene-based TE materials is generally sensitive to mechanical strain. Thus, they are more suitable for TE sensors rather than TE generators. , However, most current wearable TE materials are only flexible rather than intrinsically stretchable.…”
mentioning
confidence: 99%
“…Jang et al 54 also employed triblock copolymer to modulate the elastic properties of a ternary OTE material with a ZT value of 0.00126. In addition, OTE devices can be integrated with a free‐standing film 55 or an active matrix made of polymer insulators poly(dimethylsiloxane) (PDMS), poly(vinyl alcohol), paper, and fibers, 56–59 thereby confirming their applications in bendable and wearable attachment requirements.…”
Section: Fundamental Of Ote Materials For Smart Devicesmentioning
confidence: 98%
“…Luo et al 145 reported the preparation of CNT and block copolymer poly(ether-b-amide12) (PEBA) blended TE films, which were utilized for fabricating a flexible TEG. Firstly, PEBA was doped with LiClO 4 to prepare a PEBA-Li + solution.…”
Section: Binary Nanocomposite-based Te Materialsmentioning
confidence: 99%